Frog leg lateral view is a reliable predictor of the prognosis in osteonecrosis of the femoral head. Issue 5 (14th August 2020) - Cheng, Weike; Xian, Hang; Wang, Lei; Luo, Deqing; Huang, Zemao; Lian, Kejian; Lin, Dasheng
Abstract: The location and size of necrotic lesions are primary factors that predict the prognosis in osteonecrosis of the femoral head (ONFH). The Japanese Investigation Committee (JIC) classification system, based on the location of the necrotic lesion, has been widely accepted and applied around the world. However, there is no report about whether the location of the necrotic area in lateral view may affect the prognosis predicted initially by the JIC classification. The purpose of this study was to investigate whether the location of the necrotic area in the frog leg lateral (FL) view would affect the prediction of prognosis for patients with ONFH. We retrospectively studied 90 hips in 76 patients with ONFH (Ficat stage I to II) after a mean follow‐up of 35.3 months. All patients received standard radiographs including an anteroposterior (AP) and a FL view of the affected hip. The percentage of the necrotic area (necrotic area/whole femoral head area) was measured and compared between AP and FL view. Hips with ONFH were categorized using the JIC classification and the FL view type system, and inter‐ and intraobserver reliability was compared between them. All patients underwent personalized hip physiotherapy, and the cumulative survival rate with subsequent collapse and/or requirement for further hip surgery as the endpoints was evaluated for the two classification systems. The percentage of the necrotic area was found to be significantly greater in the FL views (47.0 ± 1.5%) than that in the AP views (37.7 ± 1.7%, P  < .01). Intraobserver reliability in the JIC classification (mean: 0.91, range: 0.85‐0.98) was higher than that in the FL view type (mean: 0.77, range: 0.63‐0.89; P  < .01), as well as the interobserver reliability in the JIC classification (mean: 0.74, range: 0.38‐0.87) was higher than that in the FL view type (mean: 0.58, range: 0.31‐0.76; P  < .01). Comparisons of survival curves showed that type III in FL view type had the worst prognosis than other two divisions, following the type II. The type I was likely to gain optimal outcomes. These findings provide evidence that the location to which necrosis extended in the FL view is a reliable indicator in predicting the prognosis of ONFH. Abstract : The location and size of necrotic lesions are primary factors that predict the prognosis in the osteonecrosis of the femoral head (ONFH). We recommend that the Japanese Investigation Committee classification is a convenient and reliable method in evaluating the ONFH. The location to which necrosis extended in the frog leg lateral view is a reliable indicator in predicting the prognosis of ONFH. It would be more helpful to add the frog leg lateral view type as a supplement in predicting the prognosis of the ONFH.